ACTION AND PROMOTION OF MENTAL HEALTH IN THE SCHOOL ENVIRONMENT: STRATEGIES AND CHALLENGES (REMUNOM, 2026)
This article aims to analyze the importance of promoting mental health in the school context, highlighting its impact on the integral development of students and the improvement of the educational environment. It also seeks to identify effective strategies for promoting mental health in schools. The understanding of health has evolved from the simple absence of disease to a broad concept of physical, mental, and social well-being. Social, political, and economic factors directly influence this condition, exposing individuals to structural vulnerabilities. In the case of adolescents, the lack of early interventions can compromise their future development, increasing exposure to emotional distress, social exclusion, discrimination, and risky behaviors. Adolescence, marked by intense transformations, makes them more susceptible to emotional challenges that can affect school performance, social relationships, and mental health. Therefore, prevention and mental health promotion programs are essential, seeking to strengthen socio-emotional skills and promote strategies for coping with stressful situations and building healthy relationships. This is a descriptive study, of the experience report type, developed from university extension activities carried out in a State School located in Teresina – Piauí. During the activity, discussion circles were held on emotions, self-esteem, and coexistence, as well os workshops on expression and relaxation strategies. Awareness campaigns on mental health and lectures and training sessions for teachers on child and adolescent mental health were also conducted. To consolidate the analyzed data, thematic categories were developed, namely: The School as a Space for Promoting Mental Health; Strategies for Promoting School Mental Health; Challenges in Implementing Mental Health Actions; and perspectives and Recommendations for Strengthening School Mental Health. Finally, the messages expressed by the students include encouragement of strength, faith, and perseverance; God is present at all times, giving courage, taking care of challenges, and ensuring that everything will be alright; encouragement to never give up on dreams, maintain faith, move forward seeking support from friends, family, and trusted people, even in the most difficult moments, we are not alone.